2017
DOI: 10.1007/s12288-017-0854-4
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Epigallocatechin Gallate on the Viability of T Lymphoblastic Leukemia Cells is Associated with Increase of Caspase-3 Level and Fas Expression

Abstract: Acute lymphoblastic leukemia is the most prevalent cancer in children. Novel components to help struggle aggressive malignancies and overcome some side effects of conventional treatments could be a promising strategy. Epigallocatechingallate (EGCG), have attracted the attention of scientists for prevention or treatment of some cancers. Jurkat cells were incubated with the different concentrations of EGCG (30-100 µm) for 24, 48, and 72 h and cell viability was investigated using MTS test. Apoptosis and the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…As the gene expression may not necessarily result in protein expression, the surface Fas was also studied. Such effects have already been reported by other plants-derived component in lymphoblastic leukemia cells (32). Pterostilbene also induces apoptosis through the caspase-independent pathway in both sensitive and chemo-resistant lymphoid leukemia cell lines (33).…”
Section: Discussionsupporting
confidence: 73%
“…As the gene expression may not necessarily result in protein expression, the surface Fas was also studied. Such effects have already been reported by other plants-derived component in lymphoblastic leukemia cells (32). Pterostilbene also induces apoptosis through the caspase-independent pathway in both sensitive and chemo-resistant lymphoid leukemia cell lines (33).…”
Section: Discussionsupporting
confidence: 73%
“…Cornwall Cull, et al have indicated that EGCG results in apoptosis in B-CLL and T-CLL cells in a dose-dependent manner, while it does not affect normal B and T cells [22]. Furthermore, it has been observed that EGCG induces apoptosis in Jurkat cell line through the expression of Fas and increasing Caspase 3 levels [23]. It has been also shown that EGCG prompts apoptosis in leukemic cells such as KG-1, TH-P1, and PML/RARα leukemic mice [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, on ALL Jurkat E6.1 cells, apoptosis was also present. Concentrations of EGCG that were used (50M, 70M, 100M) induced the apoptosis of 31%, 40%, and 71% of cells, respectively [17]. However, a chemically modified derivative of EGCG (MST-312) has been found effective as a telomerase inhibitor.…”
Section: Polyphenolsmentioning
confidence: 99%